Ascending‐dose study of noribogaine in healthy volunteers: Pharmacokinetics, pharmacodynamics, safety, and tolerability. (22nd December 2014) - Glue, Paul; Lockhart, Michelle; Lam, Fred; Hung, Noelyn; Hung, Cheung‐Tak; Friedhoff, Lawrence
Abstract Noribogaine is the active metabolite of the naturally occurring psychoactive substance ibogaine, and may help suppress withdrawal symptoms in opioid‐dependent subjects. The objectives of this Phase I study were to assess the safety, tolerability, pharmacokinetic, and pharmacodynamic profiles of noribogaine. In this ascending single‐dose, placebo‐controlled, randomized, double‐blind, parallel‐group study in 36 healthy drug‐free male volunteers, 4 cohorts (n = 9) received oral doses of 3, 10, 30, or 60 mg or matching placebo, with intensive safety and pharmacokinetic assessments out to 216 hours, along with pharmacodynamic assessments sensitive to the effects of mu‐opioid agonists. Noribogaine was rapidly absorbed, with peak concentrations occurring 2–3 hours after oral dosing, and showed dose‐linear increases of area under the concentration–time curve (AUC) and Cmax between 3 and 60 mg. The drug was slowly eliminated, with mean half‐life estimates of 28–49 hours across dose groups. Apparent volume of distribution was high (mean 1417–3086 L across dose groups). No safety or tolerability issues were identified in any cohort. No mu‐opioid agonist pharmacodynamic effects were noted in pupillometry or cold‐pressor testing. Single oral doses of noribogaine 3–60 mg were safe and well tolerated in healthy volunteers.